PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS VII MTs MATHLAÚL ANWAR KEDONDONG PESAWARAN - Nur Cholipah; Arizal Eka Putra; Mashdaria Huwaina (TABYIN: JURNAL PENDIDIKAN ISLAM, 2026)
This study aims to improve student academic achievement in the subject of Islamic Cultural History at MTs Mathla'ul Anwar Kedondong through the implementation of audiovisual media. The problem faced is the low interest in learning among students, which affects their academic performance. The research was conducted using a classroom action research (CAR) approach consisting of two cycles. Each cycle includes planning, implementation, observation, and reflection. The results of the study show that the application of the audiovisual media-based teaching method can improve students' academic achievement, as evidenced by the evaluation test results. In Cycle I, the students who achieved mastery had a percentage of 20%, with 6 students, and there was an improvement in Cycle II, where the students who achieved mastery increased to 73.33%, with 22 students..